2019
DOI: 10.1021/acschembio.9b00342
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Determinants of the Intrinsic Efficacy of the Antipsychotic Aripiprazole

Abstract: Partial agonists of the dopamine D 2 receptor 18 (D 2 R) have been developed to treat the symptoms of schizophrenia without causing the side effects elicited by antagonists. The receptor-ligand interactions that determine the intrinsic efficacy of such drugs, however, are poorly understood. Aripiprazole has an extended structure comprising a phenylpiperazine primary pharmacophore and a 1,2,3,4-tetrahydroquinolin-2-one secondary pharmacophore. We combined site-directed mutagenesis, analytical pharmacology, liga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 49 publications
(137 reference statements)
0
26
0
Order By: Relevance
“…Previous investigations suggested a crucial role for residues V91, L94, and E95 in contacting the secondary pharmacophore of bivalent D 2 R ligands, including SV-III-130. 16 , 19 In addition, W100A in extracellular loop 1 is located at the extracellular boundary of the secondary binding pocket and has been shown to affect bivalent ligand affinity and to adopt different conformations depending on the nature of the bound ligand. 13 , 27 To investigate the role of the secondary binding pocket in shaping SV-III-130 binding kinetics and insurmountability, V91, L94, E95, and W100 were individually mutated to alanine.…”
Section: Resultsmentioning
confidence: 99%
“…Previous investigations suggested a crucial role for residues V91, L94, and E95 in contacting the secondary pharmacophore of bivalent D 2 R ligands, including SV-III-130. 16 , 19 In addition, W100A in extracellular loop 1 is located at the extracellular boundary of the secondary binding pocket and has been shown to affect bivalent ligand affinity and to adopt different conformations depending on the nature of the bound ligand. 13 , 27 To investigate the role of the secondary binding pocket in shaping SV-III-130 binding kinetics and insurmountability, V91, L94, E95, and W100 were individually mutated to alanine.…”
Section: Resultsmentioning
confidence: 99%
“…More comprehensive analyses of the D2R mutants by collecting full ONC201 doseresponse curves using Go activation and cAMP inhibition assays showed that mutations of four specific residues, V91 2.61 , E95 2.65 , Y192 5.41 , and I397 6.59 , produced the most severe impact on ONC201's ability to antagonize dopamine-stimulated signaling. Notably, two of these residues, V91 2.61 and E95 2.65 , reside within a SBP formed by the interface between TMs 2 and 7 and have been shown to be involved in allosteric modulation of the D2R by bitopic and negative allosteric modulators (NAMs) (Draper-Joyce et al, 2018;Klein Herenbrink et al, 2019;Verma et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the published D3R selective ligands are common in pharmacophore consisting of a head group, which is positively charged and bear an aromatic ring, and a heteroaromatic tail connected by an apolar linker region ( Figure 3 ) [ 79 ]. This heteroaromatic tail which binds to the secondary binding pocket of the D3R is responsible for the high selectivity over the D2R (i.e., K i,D2 /K i,D3 > 100) and can fine-tune the functional character of the ligands [ 80 ]. The linker may also be important in this regard [ 81 ].…”
Section: Structure Of Dopamine D3rmentioning
confidence: 99%